Formulation and Evaluation of P-Naphthoquinone Casein Nanodispersions and their Antibacterial and Anticancer Activities - Duraikannu, Anitha Manikandan; Muthusamy, Shanmugaprakash; Rajesh, Thangavel Pichaiapaa (Indian Journal of Pharmaceutical Education and Research)
Aim/Background: This study focuses on the preparation, characterization, and evaluation of nanodispersion formulations of casein and PNQ for their antibacterial and anticancer activities. Casein micelles were used to stabilize PNQ precipitates, aiming to enhance bioavailability and therapeutic efficacy. Materials and Methods: Nanodispersion formulations were prepared and characterized using a Zeta sizer to determine particle size and stability. The average particle size ranged between 230 nm and 350 nm, with a Dynamic Light Scattering (DLS) potential of -17.6 mV to -17.2 mV, indicating stability due to casein-induced micelle formation. FTIR analysis confirmed the presence of casein-micelle-stabilized PNQ particles. In vitro drug release studies were conducted to assess the efficiency of the formulation. Results: The optimized formulation, S6, exhibited a zeta size of 229 nm, a stabilized zeta potential of -17.6 to -17.2, and a rapid drug release within 15 minutes, achieving a high drug content of 89.76±3.7%. Antimicrobial activity was observed against both E. coli and S. aureus. Cytotoxicity assay (MTT) revealed an IC50 value of 46.35±0.05 μg for the drug nanodispersion, indicating potential anticancer properties. Conclusion: The prepared PNQ nano formulation (S6) demonstrated promising antibacterial and anticancer properties by improving bioavailability and drug release. These findings suggest its potential application in treating microbial infections and cancer.
Keywords: Antibacterial; Anticancer; Casein Nanodispersion; p-Naphthoquinone.